Homelessness Prevention and Intervention in Social Work Policies, Programs, and Practices - Larkin, Heather; Aykanian, Amanda; Streeter, Calvin L. (Springer International Publishing : Imprint: Springer, 2019)
This important text provides a comprehensive survey of homelessness in America: its scope and causes, its diverse populations, and the array of responses at the individual, community, and systems levels. Expert contributors explore the links between trauma and homelessness, the cycle of homelessness and health/mental health problems, and barriers preventing people from accessing services. Case studies of effective programs and practices focus on science-based interventions, broad understanding of client needs, and close coordination between systems and agencies. Finally, specialized chapters discuss issues and experiences common to homeless youth and young adults, including housing instability on college campuses and empowerment-based strategies for engaging youth voice in programming . Included in the coverage: Homelessness and health disparities: a health equity lens Affordable housing and housing policy responses to homelessness Street talk: homeless discourses and the politics of service provision Multisectoral collaborations to address homelessness Trauma-informed care in homelessness service settings: challenges and opportunities Incorporating youth voice into services for young people experiencing homelessness Homelessness Prevention and Intervention in Social Work fills a critical gap in the social work curriculum as a main or a supplementary text. It also makes an accessible resource for clinicians and community practitioners seeking current knowledge on the topic, practical approaches to working with clients experiencing homelessness, and useful information for effective program and policy design.